2015
DOI: 10.1128/mcb.01118-14
|View full text |Cite
|
Sign up to set email alerts
|

Methylglyoxal Activates the Target of Rapamycin Complex 2-Protein Kinase C Signaling Pathway in Saccharomyces cerevisiae

Abstract: Methylglyoxal is a typical 2-oxoaldehyde derived from glycolysis. We show here that methylglyoxal activates the Pkc1-Mpk1 mitogen-activated protein (MAP) kinase cascade in a target of rapamycin complex 2 (TORC2)-dependent manner in the budding yeast Saccharomyces cerevisiae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 63 publications
2
51
0
1
Order By: Relevance
“…We acknowledge that this finding alone does not generalize the PS dependency of Pkc1 activity on the protein targets in vivo. Yet, it is known that the C1 lipidbinding domain of Pkc1 is needed for the stress-mediated activation of the MAP kinase pathway (68), and that a role for PS is supported by the attenuation of the pathway in cho1 mutant cells (62).…”
Section: Discussionmentioning
confidence: 99%
“…We acknowledge that this finding alone does not generalize the PS dependency of Pkc1 activity on the protein targets in vivo. Yet, it is known that the C1 lipidbinding domain of Pkc1 is needed for the stress-mediated activation of the MAP kinase pathway (68), and that a role for PS is supported by the attenuation of the pathway in cho1 mutant cells (62).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, methylglyoxal, a typical 2-oxoaldehyde derived from glycolysis [100], also activates the Pkc1-Mpk1 MAPK cascade; however, the methylglyoxal-induced activation of this pathway is not dependent on Wsc1/Mid2, whereas Rho1 is indispensable [101]. Besides Ypk1 and Ypk2, Pkc1 has also been identified as a direct substrate of TORC2 in S. cerevisiae, that is, Thr 1125 within the turn motif and Ser 1143 within the hydrophobic motif in Pkc1 are phosphorylated by TORC2 [101]. Methylglyoxal enhanced the phosphorylation levels of Pkc1 at Ser 1143 in a TORC2-dependent manner [101] (Figure 3).…”
Section: Itmentioning
confidence: 99%
“…A recent study reported that phosphatidylserine, one of the major glycerophospholipids prevailing in the plasma membrane, mediates the physical interaction between Pkc1 and Rho1 GTP [98,99]. On the other hand, methylglyoxal, a typical 2-oxoaldehyde derived from glycolysis [100], also activates the Pkc1-Mpk1 MAPK cascade; however, the methylglyoxal-induced activation of this pathway is not dependent on Wsc1/Mid2, whereas Rho1 is indispensable [101]. Besides Ypk1 and Ypk2, Pkc1 has also been identified as a direct substrate of TORC2 in S. cerevisiae, that is, Thr 1125 within the turn motif and Ser 1143 within the hydrophobic motif in Pkc1 are phosphorylated by TORC2 [101].…”
Section: Itmentioning
confidence: 99%
See 2 more Smart Citations